Guidelines for the Preparation of a Document Containing the Drug Safety Monitoring Results - Yu. V. Olefir; B. K. Romanov; R. N. Alyautdin; S. V. Glagolev (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
Recommendations for the Marketing Authorisation Holders for the preparation of the document containing the results of the monitoring of safety of the drug, which is presented as part of the dossier at the state registration confirmation in 5 years after the initial registration of the drug in Russia are given. Links to legal documents, and specific examples of the proper execution of the relevant sections of the document are represented.